A Language Appraisal of Hotel Web Pages in Indonesia Five Starred Hotels: Interpersonal Meaning (Universitas Islam Negeri Sunan Ampel Surabaya, 2019)
This article aims to examine the interpersonal meaning of hotel web pages using the Appraisal framework in the view of assessing the frequent occurrence of the appraisal subsystem in the text. The employment of attitudinal, graduation and engagement of text construe the alignment. They explain how the hotel introductory text construction does align the reader. Martin & White (2005) argued that appreciation reaction framework determines interpersonal significancies. The emotive prosody of this appreciation reaction is â€œit grabs meâ€, decorative, and then â€œI want itâ€ (Martin & White, 57:2005). The dominant result of appreciation resources of reaction is shown in this research than other appreciation resources. We can replace the word â€œitâ€ with the prosody of appreciation. As a result, the appreciation reaction of quality appears dominantly (44%). It means that the hotel talked much about the things: facilities and services. Finally, the interpersonal meaning of the hotel Webpages is â€˜I am the most / I am the bestâ€™. It implies that the hotel is the best in quality and services in order to attract the reader. It proves that the web pages authentically in constructing the text in order to persuade the potential customer to purchase the hotel product.